2010
DOI: 10.1051/0004-6361/200913966
|View full text |Cite
|
Sign up to set email alerts
|

GRB 021004: Tomography of a gamma-ray burst progenitor and its host galaxy

Abstract: Aims. We analyse the distribution of matter around the progenitor star of gamma-ray burst GRB 021004 and the properties of its host galaxy with high-resolution echelle and near-infrared spectroscopy. Methods. Observations were taken by the 8.2 m Very Large Telescope with the Ultraviolet and Visual Echelle spectrograph (UVES) and the Infrared Spectrometer And Array Camera (ISAAC) between 10 and 14 h after the onset of the event.Results. We report the first detection of emission lines from a GRB host galaxy in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…2) associated to the GRB 021004 host galaxy. These detections confirm the tentative identification presented by Castro-Tirado et al (2010). The redshift measured from the [O III] doublet and Hα lines is z = 2.33102: we refer to this value as the host galaxy redshift.…”
Section: The Host Galaxysupporting
confidence: 88%
See 1 more Smart Citation
“…2) associated to the GRB 021004 host galaxy. These detections confirm the tentative identification presented by Castro-Tirado et al (2010). The redshift measured from the [O III] doublet and Hα lines is z = 2.33102: we refer to this value as the host galaxy redshift.…”
Section: The Host Galaxysupporting
confidence: 88%
“…Their nature is still debated. Many authors (e.g., Schaefer et al 2003;Mirabal et al 2003;Fiore et al 2005;Castro-Tirado et al 2010) claim that at least some of them originated from the wind of the Wolf-Rayet star whose death produced the GRB. This would be a very important result because it could be the first direct association of a GRB with its progenitor.…”
Section: Introductionmentioning
confidence: 99%
“…high redshifts. In particular, they enable investigations of the ISM in terms of chemical abundances Prochaska et al 2007;Cucchiara et al 2015), dust content (Savaglio et al 2003;Schady et al 2010;Zafar et al 2011;Zafar & Watson 2013), kinematics (Prochaska et al 2008a;Arabsalmani et al 2015Arabsalmani et al , 2018, and the very local circumburst medium (Møller et al 2002;Prochaska et al 2006Prochaska et al , 2008bFox et al 2008;Castro-Tirado et al 2010;Schady et al 2011). The large majority of GRB afterglow spectra show damped Lyman-α (DLA) absorption, i.e., a neutral hydrogen column density of N(H i) > 2 × 10 20 cm −2 (Vreeswijk et al 2004;Jakobsson et al 2006;Fynbo et al 2009;Cucchiara et al 2015, and Tanvir et al, submitted), typically with higher H i column densities than seen in DLAs toward quasars (e.g.…”
mentioning
confidence: 99%
“…The omnipresence of line locking in different wind conditions, also suggests that radiative acceleration might be a dominant effect in other environments. These could be the outflows from gamma-ray bursts (Castro-Tirado et al 2010), quasar jets (Gravity Collaboration et al 2017), or Seyfert galaxies, where line locking has been suggested and tentative detections have been reported. Finally, the fact that line locking is observed for the Civ doublet but not for other species may be connected to the physical properties of a characteristic multiphase structure in the outflow, where different species trace different regions.…”
Section: Resultsmentioning
confidence: 99%